Iowa Birdline update, circa September 6, 1988 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1988)
Notes for the Iowa Birdline update for circa September 6, 1988. Highlights of the update include sightings of a Western Tanager, Merlins, Sandhill Cranes, Caspian Terns, a Yellow-billed Cuckoo, and several Heron species. Also of note was the report of excellent shore birding from Hendrickson Marsh Lake, including sightings of three Red-necked Phalaropes and two species of Sandpipers. Epson - sheet feed